ACCOUNTING FOR CURRENT DEPRECIATION. - Mason, Perry (The Accounting Review, 1930)
Abstract Depreciation may be defined as that inevitable disappearance of the value of certain items of physical property which can normally be expected in the course of the conduct of business enterprises. The reason why the unit is no longer of value to the owner may be actual physical deterioration, or it may be that changes in demand for the product of a machine or technical improvements of one kind or another have made the unit obsolete. The accounting problem in connection with depreciation, is to record in some way the amount of depreciation which should be taken in each accounting period and this amount in turn may have to be spread over several products or services which were produced or were in process during the period. Much of the disagreement in the discussions of depreciation reserves has undoubtedly been partially caused by the use of only one reserve for depreciation for the entire property instead of one reserve for each type of property. A great deal of confusion concerning depreciation arises from the interpretation of the depreciation policy as a means of providing for or facilitating the making of replacements.